Residue analysis of the fumigant pesticide ethanedinitrile in different agricultural commodities using ether extraction and GC-MS. (September 2019) - Ramadan, Gomaa R.M.; Abdelgaleil, Samir A.M.; Shawir, Mohamed S.; El-bakary, Ahmed S.; Edde, Peter A.; Phillips, Thomas W.
Abstract: Ethanedinitrile (EDN) is used to fumigate logs and timber products, and it has the potential as an alternative fumigant for stored food products. Other work has demonstrated efficacy of EDN for controlling stored grain pests, but information on EDN residues in food commodities are needed to assess impacts on food safety. The present study developed and validated a method to determine EDN residues in whole wheat kernels, wheat flour, whole corn kernels, pinto beans and dried whole-leaf tobacco. EDN was extracted from commodities with diethyl ether and analyzed by quantitative GC-MS in selected ion monitoring (SIM). The method achieved a high level of selectivity and good precision with acceptable recoveries between 42.3 and 96.6% and relative standard deviation (RSD) < 20% when known concentrations were set at 0.00594, 0.0594 and 0.594 mg/L. The limit of detection (LOD) and limit of quantitation (LOQ) were 0.001 and 0.003 mg/L, respectively. Also, the actual residues of EDN were evaluated in the commodities at two levels of fumigation and after different aeration times. The initial deposits of EDN residues after 1 h ranged from 32.08 to 100.60 μg/kg following fumigation with 2.6 mg/L, and 56.30–154.78 μg/kg when fumigated at 4.8 mg/L. The dissipation of EDN in the fumigated commodities followed the first order kinetics model with half-life values ranged from 6.47 to 36.47 h at 2.6 mg/L and from 21.6 to 57.75 h at 4.8 mg/L. This research demonstrates that ether extraction followed by GC-MS generates useful residue data from EDN in grains and tobacco, and those residues can vary widely among these products. These findings are important as work moves forward to adopt EDN as a stored product fumigant. Highlights: Ethanedinitrile, EDN, has potential as an alternative fumigant for stored products. EDN residue studies were conducted on five commodities following controlled fumigations. Commodities were extracted with diethyl ether followed by quantitative GS-MS analysis. EDN residues were very low at 1 h after fumigation suggesting EDN could be safe for foods.